Analysis of the Effectiveness of the Romaco Killian KTP 720X Machine Using the Overall Equipment Effectiveness Method at PT XYZ - Mutiara Handayani; Yulia Nuraeni; Wawan Wijaya Kusumah; Tiaradia Ihsan (Sean Institute, 2026)
The effectiveness of production machinery is one of the key factors determining the success of manufacturing processes, particularly in the pharmaceutical industry, which demands high accuracy and consistent product quality. PT XYZ utilizes the Romaco Killian KTP 720X as one of its main machines in the tablet compression process. However, during the period from January to September, the machine's production output did not meet the company’s target. This condition highlights the need for a systematic evaluation of the machine’s performance. This study was conducted using the Overall Equipment Effectiveness (OEE) method, a comprehensive indicator used to assess machine effectiveness based on three main components: availability, performance, and quality. Production data were collected through direct observation, company documentation, and interviews, covering loading time, downtime, operation time, actual output, number of defective products, and the machine’s ideal cycle time. The results show that the machine’s average availability was 68.00%, performance was 29.14%, and the quality rate reached 99.11%. These components generated an OEE value of 19.52%, which is significantly below the international standard of 85% established by the Japanese Institute of Plant Maintenance (JIPM). The low OEE value is primarily attributed to the performance component, which falls far below the required standard, indicating that the machine does not operate at its ideal speed. These findings underscore the need to improve process efficiency, optimize machine speed settings, and evaluate operational procedures to enhance machine performance and ensure the achievement of the company's production targets.